PEMANFAATAN EKSTRAK DAUN PEGAGAN (CENTELLA ASIATICA L.) DALAM PEMBUATAN KOSMETIK FACE MIST UNTUK KULIT WAJAH KERING - Claudia Mailanda Salsabila; Prima Minerva (Ensiklopedia of Journal, 2025)
Dry skin occurs when the outermost layer of skin loses its moisture, resulting in roughness, itching, and cracking. Face mist is a cosmetic preparation formulated for dry skin types and is useful for increasing the hydration of the skin's outer layer. Gotu kola (Centella asiatica L.) contains various active compounds beneficial for dry skin, such as flavonoids as antioxidants and moisturizers, vitamin C which can help brighten dull skin, asiaticoside which stimulates collagen production, madecassoside which maintains skin moisture, asiatic acid which has antioxidant effects, and madecassic acid which increases the skin's natural ceramide production. This research endeavors to formulate a face mist utilizing Centella asiatica (gotu kola) leaf extract, tailored for individuals with dry skin.A descriptive quantitative method was employed, integrating an experimental design. The extraction of gotu kola leaves was executed via maceration using 96% ethanol as the solvent.Three variations of concentrations were formulated: F1 (1%), F2 (1.5%), and F3 (2%). Physical properties were assessed through laboratory tests, examining vitamin C levels, uniformity, pH balance, spreadability, and drying time.Organoleptic evaluations—covering texture, color, and scent—were conducted, alongside hedonic assessments to gauge panelist preferences.Results confirmed the mist contained vitamin C, exhibited homogeneity, had a standard pH range (4.5–6.5), showed effective spreadability, and dried in under five minutes.Among the tested formulas, F2 emerged as the most favored based on sensory and preference tests.Consequently, gotu kola extract demonstrates strong potential as an active component in face mist products designed for dry skin care.Keywords: gotu kola leaf, face mist, dry skin, cosmetics